Centro cultural en San Juan de Lurigancho - Ramírez Mendoza, Cristian Fernando (2018)
El centro cultural SJL provee áreas de reunión y difusión de arte a través de exhibiciones y enseñanza. El proyecto resuelve tres cuestiones importantes para su función y sustento: primero, ofrece espacios para el desarrollo de programas culturales, administrativos y comerciales. Segundo, adecúa el proyecto a los limitados recursos económicos disponibles para su construcción. Y tercero, satisface la necesidad de espacio público tan escaso en SJL. Entonces, el centro cultural contribuirá al tejido sociocultural de la comunidad luriganchina. The Cultural Centre SJL provides spaces for the promotion of art through exhibitions and teaching, as well as a social area. The project solves three essential issues for its functioning and subsistence: first, it offers spaces for its cultural, administrative and commercial activities. Second, it adjusts to the limited financial resources for its construction. And third, it supplies a much-needed public space in SJL. Thus, the cultural center will contribute to the social and cultural development of the Luriganchina community.